In vitro evaluation of disposable transport ventilators with combination aerosol therapy - Mac Giolla Eain, Marc (BMJ Open Respir Res, 2021)
BACKGROUND: The COVID-19 pandemic has highlighted the need for alternative short-term, reliable means to aid in the treatment of patients requiring ventilatory support. Concurrent aerosol drug delivery is often prescribed to such patients. As such, this study examines one such short-term option, the disposable gas-powered transport ventilator to effectively deliver aerosol therapy. Factors such as aerosol generator type, patient breathing pattern, humidification and nebuliser position within the respiratory circuit were also examined. METHODS: Aerosol drug delivery characterisation was undertaken using two different disposable transport ventilators (DTVs). Two different nebuliser types, a closed circuit vibrating mesh nebuliser (VMN) and an open circuit jet nebuliser (JN), at different locations in a respiratory circuit, proximal and distal to an endotracheal tube (ETT), with and without passive humidification, were evaluated in simulated adult and paediatric patients. RESULTS: Placement of a nebuliser proximal to the ETT (VMN: 25.19%–34.15% and JN: 3.14%–8.92%), and the addition of a heat and moisture exchange filter (VMN: 32.37%–40.43% and JN: 5.60%–9.91%) resulted in the largest potential lung dose in the adult patient model. Irrespective of nebuliser position and humidification in the respiratory circuit, use of the VMN resulted in the largest potential lung dose (%). A similar trend was recorded in the paediatric model data, where the largest potential lung dose was recorded with both nebuliser types placed proximal to the ETT (VMN: 8.12%–10.89% and JN: 2.15%–3.82%). However, the addition of a heat and moisture exchange filter had no statistically significant effect on the potential lung dose (%) a paediatric patient would receive (p>>0.05). CONCLUSIONS: This study demonstrates that transport ventilators, such as DTVs, can be used concurrently with aerosol generators to effectively deliver aerosolised medication in both adult and paediatric patients.